Comparative Assessment of Drinking Water Quality: An Investigation of Physicochemical and Microbial Characteristics - Jonah, Udeme Effiong; FRIDAY MENDIE, CECILLIA (Journal of Science and Technology, 2025)
Water pollution has been the major challenges in Nigeria. The consumption of contaminated water threatens the health and livelihoods of citizens. The study assesses the suitability of drinking water sources in Ikot Ekpene metropolis using physiochemical and microbial characteristics. Water samples were collected monthly between April 2023 and November 2023 in six drinking water sources; the samples were analyzed using standard laboratory techniques. The results revealed that the mean value of NO2 in sachet and surface water and the pH value in surface water were deviated from Nigerian drinking water quality standard. The THBC values in sachet water ranged between 1.0 and 3.0 cfu/100mL, while surface water ranged between 24.0 and 167.0 cfu/100mL; the TCC ranged from 0.0 to 2.0 cfu/100mL in sachet water and 12.0 to 66.0 cfu/100mL in surface water; the TSBC ranged from 5.0 to 17.0 cfu/100mL in sachet water and 5.0 to 59.0 cfu/100mL in surface water, while TFCC values in sachet water ranged from 0.0 to 3.0 cfu/100mL and 6.0 to 50.0 cfu/100mL in surface water. The mean values of TSBC and TFCC (sachet water) and THBC, TCC, TSBC, TFCC (surface water) exceeded the limits for Nigerian drinking water quality. The Clostridium spp was the most abundant in surface water, while Staphylococcus spp was in sachet water samples. The WQI value was higher (67.0) in surface water compared with the 5.58 recorded in sachet water. The study revealed that the surface water is polluted compared with the sachet water, and not suitable for human consumption, owing to the prevalence of microbial parameters attributed to anthropogenic activities.